Do Invasive Mosquito and Bird Species Alter Avian Malaria Parasite Transmission? - Josué Martínez-de la Puente; Alazne Díez-Fernández; Tomás Montalvo; Rubén Bueno-Marí; Quentin Pangrani; Ramón C. Soriguer; Juan Carlos Senar; Jordi Figuerola (Diversity, 2020)
Alien mosquito and vertebrate host species may create novel epidemiological scenarios for the transmission of pathogens naturally circulating in the invaded area. The exotic Monk parakeet (Myiopsitta monachus) has established populations in Europe and is currently considered an invasive pest. Due to their high abundance in urban areas, Monk parakeets could be involved in the transmission of pathogens, potentially affecting wildlife and livestock. To test this hypothesis, we determined the prevalence and diversity of three vector-borne parasites, namely Plasmodium, Haemoproteus and Leucocytozoon, in Monk parakeets from Barcelona. Many areas of southern Europe shelter high densities of the invasive Asian tiger mosquito Aedes albopictus, which in addition to native mosquito species could affect the transmission of mosquito-borne parasites, such as avian Plasmodium. Thus, we also sampled mosquitoes in the area to trace their blood-feeding hosts and determine the presence of Plasmodium parasites. Monk parakeets were neither infected by Plasmodium nor by Haemoproteus parasites, and only five individuals (3.13%; n = 160) were infected by Leucocytozoon. Monk parakeets were bitten by Culiseta longiareolata and represented 9.5% of Culex pipiens blood meals. The invasive Ae. albopictus showed a clear anthropophilic feeding pattern, with humans dominating its diet. Three Plasmodium lineages were detected in pools of Cx pipiens. These results suggest that Plasmodium circulating in the area cannot develop in the invasive Monk parakeet, in spite of the relatively high fraction of native mosquito vectors feeding on this species in its invaded distribution range.